Thrombus aspiration without stenting in a patient with anterior STEMI: Regression and healing of an unstable plaque assessed by OCT at 24 months of follow‐up. Issue 8 (15th August 2021) - Babunashvili, Avtandil; Pancholy, Samir; Babunashvili, Tamara; Prokhorov, Alexander
Abstract: In selected cases, when STEMI caused by mild or moderate degree lesion with a large concomitant thrombus, additional OCT‐guided PCI strategy after thrombus removal allows us to defer stenting with the follow‐up natural healing of the vessel wall. Abstract : In selected cases, when STEMI caused by mild or moderate degree lesion with a large concomitant thrombus, additional OCT‐guided PCI strategy after thrombus removal allows us to defer stenting with the follow‐up natural healing of the vessel wall.